Vilém Flusser : au croisement de l’image technique et de la mode - Luciana Nacif (Appareil)
In this text, I intend to link Flusser’s concepts on the technical image to the technological innovations of the 21st century. And then discuss the impact of the proliferation of technical images on the field of fashion. Flusser argues that, in Post-history, technical images have become a model of life, and an entire culture has formed around their creation, distribution, and consumption. He rejects the conception of photography as representation and believes that the purpose of the camera is to influence the way we perceive the world, by programming our behavior. The arrival of digital images has contributed to questioning the concept of representativeness of analog images. Moreover, the digital image is only partially an image in the classical sense : it has also become an element of data flow on the network, and its “invisible” aspects have caused profound ontological changes. In that regard politics enters the visual field not only at the level of representation, but also at the structural level of its acquisition, processing and transmission. In fashion, we see the post-industrial logic operating, whereby the object loses its value and the image is what counts. Thanks to machines for creating and duplicating images, we acquire information rather than experiences. This is how fashion images shape our way of seeing the world, defining values, behaviors, forging identities. Today we see our attention leaving the singular photographic image and getting used to sequences of images, in an inexhaustible flow that makes it difficult to develop an intimate relationship with a single image. The guarantee of endless online fun encourages the relentless pursuit in which the present image is just a cover for the next, potentially more exciting one.